POTENSI TALAS BENENG (Xanthosoma undipes) UNTUK MENINGKATKAN PRODUKTIVITAS HUTAN RAKYAT DI CIAMIS, JAWA BARAT - Suhartono, Suhartono (Creative Research Journal, 2024)
The productivity of community forests is still low when measured on an annual average. It is caused by exploitation that still relies on wood products. Therefore, developing agricultural commodities with high economic value could be a solution to increasing the productivity of community forests. This research aimed to analyse the potential of taro beneng to increase the productivity of community forests and how much land has the potential for its development. We conducted surveys and interviews with two key informants (head of the beneng-taro farming group in Sukamaju Village and Kutawaringin Village, Ciamis Regency) and literature studies from various sources on the internet. A spatial analysis was conducted to calculate the potential land area for developing beneng taro in community forests. The results of this study showed that beneng taro has the potential to be developed in community forest land because it is shade-tolerant, easy to cultivate, has a high production of tubers and leaves, and has export opportunities. The total area of land that has the potential for developing taro beneng in Ciamis Regency reaches 35,260.05 ha, consisting of categories from moderately suitable to highly suitable, spread across 26 sub-districts.